(untitled) (Biomedical Research and Therapy, 2023)
Introduction: The role of Tridax procumbens leaf extract in erectile dysfunction (ED) of chronic variable stress (CVS) etiology is unknown. This study investigates the potential of the ethanol fraction of Tridax procumbens leaf (EETP) in modulation of CVS-induced ED. Methods: Twenty-five male Wistar rats were divided into five groups of five rats each. Groups 1 & 2 (without stress) were treated with normal saline (vehicle) and 100 mg/kg of EETP, respectively. Groups 3?5 were treated as stress groups, with Group 3 co-treated with 100 mg/kg of EETP, and group 4 co-treated with vitamin C (7 mg/kg). Treatments were administered by oral gavage once daily for seven weeks. Oxidative biomarkers, cortisol, testosterone, and sperm parameters were determined, as well as the contractile mechanism of the corpus cavernosa to cumulative doses of calcium chloride, potassium chloride, acetylcholine, and sodium nitroprusside. Furthermore, the contractile mechanism was also determined after incubation in acetovanillone, nicorandil, methyl blue, and glibenclamide. Results: Serum cortisol was significantly reduced, while testosterone was significantly increased in the EETP supplemented groups when compared to the CVS-only exposed group. Furthermore, malonaldehyde activity was decreased while superoxide dismutase concentration was increased in the EETP- and vitamin C-supplemented groups when compared to the CVS-only exposed group. Contraction (%) responses to calcium chloride and potassium chloride were also significantly reduced in the CVS-only exposed group when compared to the EETP-supplemented groups. The relaxation responses (%) to acetylcholine and SNP were significantly increased in the CVS group supplemented with EETP and vitamin C when compared to the CVS-only exposed group. The incubation of the cavernosa tissues in acetovanillone and nicorandil resulted in increased relaxation (%) in the CVS-only group, while incubation in glibenclamide caused increased relaxation in the EETP-supplemented groups compared to CVSonly exposed group. Sperm motility (%) was significantly reduced while abnormal spermatozoa was increased in the CVS-only exposed group when compared to the groups supplemented with EETP and Vitamin C. Conclusion: Variable stress-induced dysfunctions in erectile mechanism were attenuated through supplementation with EETP.